THE ORGANIZATION OF THE SOVIET PRESS IN TURKESTAN - Namazova Nilufar (Bright Mind Publishing, 2025)
The article examines the processes of closing the new press in Turkestan (Uzbekistan) and replacing it with the Soviet press. It analyzes the assistance of the Jadid intelligentsia and the colonial attitude of the Bolsheviks to the Uzbek press.
Keywords: Soviet press, Jadids, Bolsheviks, Orif Klebleev, class struggle.